ANALISIS PENDAPATAN USAHATANI SAWO (Manilkara zapota L.) DI DESA API-API KECAMATAN WARU KABUPATEN PENAJAM PASER UTARA - Midiansyah, Firda Juita, Aditya Rachman Yusuf (LPPM University 17 Agustus 1945 Samarinda, 2022)
Sapodilla is a long-lived fruit tree, sapodilla is very beneficial for health, people really like sapodilla because the fruit is sweet and soft. Sapodilla farming activities carried out are activities to produce agricultural commodities as agribusiness. This study aims was to determine the income from sapodilla farming in Api-Api Village, Waru District, North Penajam Paser Regency. This research has been carried out for 3 months from December 2020 to February 2021 in Api-Api Village, Waru District, Pejanam Paser Utara Regency. Sampling using the census method or saturated sample with a total of 29 respondents. The data collection method used primary data with interviews and secondary data with relevant literature after which income was analyzed. The results showed that the average total revenue obtained by the respondents was IDR 4.840.127.000 ha-1 year-1 with an average revenue of IDR 166.900.931,03 ha-1 year-1 while the production cost was IDR 673.376.000 ha-1 year-1 with an average production cost of IDR 23.219.862,07 ha-1 year-1 The results of the analysis show that the total income obtained from 29 respondents is IDR 4.166.751.000 ha-1 year-1 with an average income IDR 143.681.068,97 ha-1 year-1 . The role of the government is very important to encourage sapodilla farming to increase maximum yields.